Identification of Soil Bacterial Isolates Suppressing Different Phytophthora spp. and Promoting Plant Growth - Syed-Ab-Rahman, Sharifah Farhana; Carvalhais, Lilia C.; Chua, Elvis; Xiao, Yawen; Wass, Taylor J.; Schenk, Peer M. (Frontiers in Plant Science, 2018)
Bacterial isolates obtained from the rhizosphere of Arabidopsis and a plantless compost potting mix were screened for anti-oomycete activity against Phytophthora capsici, Phytophthora citricola, Phytophthora palmivora and Phytophthora cinnamomi. Three out of 48 isolates exhibited more than 65% inhibition against all tested Phytophthora species and were selected for further studies. These strains, named UQ154, UQ156 and UQ202, are closely related to Bacillus amyloliquefaciens, Bacillus velezensis and Acinetobacter sp., respectively, based on 16S rDNA sequence analysis. The isolates were evaluated for their ability to fix nitrogen, solubilize phosphate, as well as for siderophore, indole acetic acid, cell wall degrading enzymes and biofilm production. Their plant growth promoting activities were evaluated by measuring their effect on the germination percentage, root and shoot length, and seedling vigour of lettuce plants. All of these traits were significantly enhanced in plants grown from seeds inoculated with the isolates compared with control plants. Moreover, bacteria-inoculated P. capsici-infected chilli plants exhibited improved productivity based on CO2 assimilation rates. Both real-time quantitative PCR and disease severity index revealed significant decreases in pathogen load in infected chilli root tissues when plants were previously inoculated with the isolates. Biocontrol activity may result from the secretion of diketopiperazines as identified by Gas Chromatography-Mass Spectrometry analysis of bacterial cultures’ extracts. Collectively, this work demonstrates the potential of bacterial isolates to control Phytophthora infection and promote plant growth. They can, therefore be considered as candidate microbial biofertilizers and biopesticides.